Feasibility analysis of total quality management in medical quality management and its impact on work efficiency - Shi, Peiyao (Frontiers in Medicine, 2025)
ObjectiveThis study aimed to analyze the feasibility of total quality management (TQM) in medical quality management (focusing on three dimensions: management work efficiency, medical service quality, and safety quality) and to evaluate its impact on the work efficiency of medical staff.MethodsTQM was introduced in January 2023, serving as the dividing point between the pre-management period (January-December 2022) and the post-management period (January-December 2023). Fifty medical staff members from the same cohort were chosen as study subjects. Comparisons were made between the pre- and post-management periods in terms of work efficiency (hospital culture development, reward and punishment mechanisms, communication and coordination mechanisms, environmental hygiene management mechanisms, and adverse event reporting mechanisms), medical service quality, staff satisfaction, safety quality (incidence of adverse events, unplanned returns to the operating room, qualification rate of medical device sterilization, incidence of infection events, and medical complaints), and overall medical quality (medical safety management, medical training management, and medical hygiene supervision). Data were analyzed using SPSS 29.0. Paired-sample t-tests were employed for continuous variables (scale scores), while χ2 tests were used to categorical variables (satisfaction, safety quality).ResultsAfter TQM implementation, the work efficiency of medical staff significantly increased (P < 0.001). Compared to the pre-management period, the post-management period exhibited higher medical service quality scores, greater overall staff satisfaction, lower incidences of adverse events, unplanned returns to the operating room, infection events, and medical complaints, a higher sterilization qualification rate for medical device, and enhanced medical safety, training, and hygiene supervision management (all P < 0.05).ConclusionTQM is feasible and effective in medical quality management. Its implementation can enhance work efficiency and medical service quality among medical staff, improve satisfaction, strengthen safety quality, and comprehensively elevate overall medical quality.